Teacher educators' interpretation and practice of learner-centred pedagogy : a case study - Nyambe, Kamwi John (Rhodes University, Faculty of Education, Department of Education)
The objective of this study was to understand how teacher educators in a Namibian college of education interpret and practice the learner-centred pedagogy underpinning the Basic Education Teachers Diploma (BETD) program. In order to achieve this objective, a case study approach was adopted, qualitative-interpretive in orientation and drawing upon interviews, naturalistic non-participant observation and document analysis. Bernstein's theory of pedagogy - in particular his notion ofrecontextualization - offered ideas and concepts that were used to generate and analyse data. The data indicated that, at the level of description, teacher educators interpreted leamercentred pedagogy as a pedagogic practice based on weak rules of regulative discourse, or a weak power relation between themselves and their student teachers. The weakening of the rules of regulative discourse and the waning of educator authority were indicated in the interview narratives, which evoked a pedagogic context characterized by a repositioning of the student teacher from the margins to the centre of the classroom, where he or she enjoyed a more active and visible pedagogic position. Contrary to the dis empowering dynamic within classroom practice under the apartheid dispensation, the repositioning of the student teacher suggested a shift of power towards him or her. Similarly, the identification of the teacher educator as afacilitator, which featured prominently in the interview narratives, further suggested a weakening or diminishing of the pedagogic authority of the teacher educator. With regard to rules pertaining to the instructional discourse, the data revealed an interpretation of leamer-centred pedagogy as a pedagogic practice based on strong framing over the selection of discourses, weak framing over pacing, and strong framing over sequencing and criteria for evaluation. When correlated with the interview data, the data generated through lesson observation and teacher educator prepared documents such as lesson plans revealed a disjuncture between teacher educators' ideas about leamer-centred pedagogy and their practice of it. Contrary to the interviews, lesson observation data revealed that teacher educators implemented leamer-centred pedagogy as a pedagogic practice based on strong internal framing over rules of the regulative discourse. Data further indicated strong internal framing over the selection, sequencing, pacing and evaluation. The study concluded that while some teacher educators could produce an accurate interpretation oflearner-centred pedagogy at the level of description, most of them did not do so at the level of practice. Findings revealed structural and personal-psychological factors that constrained teacher educators' recontextualization of the new pedagogy. A narrow understanding of leamercentred pedagogy that concentrated only on changing teacher educators' pedagogical approaches from teacher-centred to learner-centred, while ignoring structural and systematic factors, tended to dominate not only the interview narratives but also official texts. Learner-centred pedagogy was understood as a matter of changing from teachercentredness to leamer-centredness while frame factors, for instance regarding the selection, pacing or sequencing of discourses, still followed the traditional approach. The study recommends the adoption of a systematic and deliberate approach to address the multiplicity of factors involved in enabling teacher educators to interpret and implement leamer-centred pedagogy at the micro-level of their classrooms.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Bernstein, Basil B; Education -- Philosophy; Education (Higher) -- Namibia; Teacher educators -- Namibia -- Case studies; Universities and colleges -- Namibia -- Case studies; Teachers -- Traning of -- Namibia -- Case studies; Teachers -- In-service training -- Namibia; Student-centered learning -- Namibia